ANALYSIS OF POTENTIAL CONTAMINATION RISKS IN THE BEVERAGE PRODUCTION PROCESS OF TASTEA OUTLET URIPSUMIHARJO MAKASSAR WITH THE SUPPLY CHAIN OPERATION REFERENCE (SCOR) AND HOUSE OF RISK (HOR) APPROACHES - Rania, Andi; Nusran , Muhammad; Hafid , Muhammad Fachry (Komunitas Menulis dan Meneliti (Kolibi), 2024)
The beverage industry in Indonesia continues to experience significant growth every year, with a growth of 3.57 percent in the third quarter of 2022 compared to the same period the previous year. Contemporary beverages, such as bubble tea, iced coffee milk, and milktea, are the main trends in the Indonesia beverage market which are synonymous with innovation and ease of consumption. Amid its popularity, contemporary beverages face new challenges related to the risk of contamination during production, storage, and distribution. This research focuses on the Tastea outlet in Uripsumiharjo, Makassar, as a case study that represents a common practice in the industry. Tastea has problems in the form of variations in customer requests that are often complicated can increase the risk of errors in handling ingredients and serving beverages, therefore it is necessary to conduct a contamination risk analysis including evaluation of tastea outsourcing management, raw materials, sanitation procedures, and the use of serving tools. By applying the Supply Chain Operation Reference (SCOR) and House of Risk (HOR) methods, the research aims to identify and reduce potential contamination risks in the supply chain as well as improve the safety and quality of beverages served to customers. Based on the SCOR model, the analysis includes the process of planning, material receipt, manufacturing, delivery, and return. Key risks include misplanning production, facility unpreparedness, and transportation issues that can disrupt daily stock availability. Meanwhile, from risk identification, 18 potential risks were identified by severity and event assessment. This includes changes in demand, transportation disruptions, lack of sterilization, and problems with beverage ingredients.